The last man on Earth. The complete third season [videorecording (DVD)] - Solomon, John, 1970-; Atencio, Peter; Forte, Will; Schaal, Kristen; Jones, January, 1978- (Twentieth Century Fox Home Entertainment, 2018)
After a deadly virus wipes out the entire population of the Earth, Phil Miller is the only man left alive and he desperately tries to find other survivors.